Penanaman Pohon Mangrove di Area Tepi Pantai dalam Rangka Meminimalisir Dampak Sedimentasi Air Laut - Poalahi Salu, Sahrul; Rembah, Rina; A, Arif; H, Hasriyanti; N, Nurfasiha; Kumalasari, Rizky (Idea Pengabdian Masyarakat, 2023)
Mining is one of the activities that use natural resources. Mining activities can have both positive and negative impacts on local governments and communities. The positive impacts can lead to an increase in regional income, while the negative impacts are reduced land activity, erosion, landslides and disturbance of flora and fauna. The knowledge of the people living around the mining area about the impact of mining activities has a major impact on environmental sustainability. This community service was conducted at Sulaho Village, IV Lanipa-nipa Hamlet, Lasusua District, North Kolaka Regency. The service method is carried out with lectures/socialization of the planting technique procedures as well as the direct planting of mangrove trees in the beach area. As a result of the engagement, the team received active responses from the community by asking questions, great enthusiasm for participating in direct field planting activities, and commitment to always protect the surrounding area from the negative impacts that mining activities could cause. All parties involved in mining activities are expected to participate in protecting the environment around the mining area